Tenofovir disoproxil fumarate and emtricitabine maintenance strategy in virologically controlled adults with low HIV-1 DNA: 48 week results from a randomized, open-label, non-inferiority trial. (16th March 2021) - Prazuck, Thierry; Verdon, Renaud; Le Moal, Gwenaël; Ajana, Faïza; Bernard, Louis; Sunder, Simon; Roncato-Saberan, Mariam; Ponscarme, Diane; Etienne, Manuel; Viard, Jean-Paul; Pasdeloup, Thierry; Darasteanu, Iuliana; et al.
Abstract: Objectives: Low HIV reservoirs may be associated with viral suppression under a lower number of antiretroviral drugs. We investigated tenofovir disoproxil fumarate/emtricitabine as a maintenance strategy in people living with HIV (PLHIV) with low HIV-DNA. Methods: TRULIGHT (NCT02302547) was a multicentre, open-label, randomized trial comparing a simplification to tenofovir disoproxil fumarate/emtricitabine versus a triple regimen continuation (tenofovir disoproxil fumarate/emtricitabine with a third agent, control arm) in virologically suppressed adults with HIV-DNA <2.7 log10 copies/10 6 PBMCs and no prior virological failure (VF). The primary endpoint (non-inferiority margin 12%) was the percentage of participants with a plasma viral load (pVL) <50 copies/mL in ITT (Snapshot approach) and PP analyses at Week 48 (W48). Results: Of the 326 participants screened, 223 (68%) were randomized to the tenofovir disoproxil fumarate/emtricitabine arm ( n = 113) or control arm ( n = 110). At W48, the tenofovir disoproxil fumarate/emtricitabine and control arms maintained a pVL < 50 copies/mL in 100/113 (88.5%) and 100/110 (90.9%) participants, respectively (ITT difference 2.4%, 95% CI –5.9 to 10.7; PP difference 3.4%, 95% CI –4.2 to 11.0). Six VFs occurred in the tenofovir disoproxil fumarate/emtricitabine arm (two with emerging mutations M184V and K65R) versus two in the control arm (ITT difference 3.5%, 95% CI –1.9 to 9.4). All VFs were resuppressed after treatment modification. Conclusions: Although non-inferiority was shown, simplification to tenofovir disoproxil fumarate/emtricitabine should not be used for most PLHIV because of a low risk of VF with resistance.